PENGARUH QUALITY OF WORK LIFE (QWL), KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (Studi Empiris pada Badan Kepegawaian Daerah Provinsi Jawa Tengah) - Noviana Rinjani, 14.05.51.0048; Rahayuningsih, Sri (Students Journal of Economic and Management, 2018)
The purpose of this study was to analyze the influence of Quality of Work Life (QWL), competence and work discipline on the employee performance at Badan Kepegawaian Daerah of Central Java Province. In this study the independent variables that affect employee performance is limited toQuality of Work Life (QWL), competence and work discipline. The population in this study is the total employee Badan Kepegawaian Daerah of Central Java Province amounting to 182 people. In this study, using sampling with Simple Random Sampling technique and and elected as many as 92 respondents are used as a sample. The data collection through primary data by distributing questionnaires to the respondents as well as secondary data from archives owned by instance and literature studies. Data testing technique used include data feasibility test, model feasibility test, multiple linear regression analysis and hypothesis test t-test. The result of the research shows that Quality of Work Life (QWL) has a positive and significant impact on the employee performance at Badan Kepegawaian Daerah of Central Java Province. Competence has a positive and significant impact on the employee performance at Badan Kepegawaian Daerah of Central Java Province. Work discipline has a positive and not significant impact on theemployee performance at Badan Kepegawaian Daerah of Central Java Province.Keywords : Quality of Work Life (QWL), competence, work discipline and employee performance